2021
DOI: 10.2196/22774
|View full text |Cite
|
Sign up to set email alerts
|

Procedures of User-Centered Usability Assessment for Digital Solutions: Scoping Review of Reviews Reporting on Digital Solutions Relevant for Older Adults

Abstract: Background The assessment of usability is a complex process that involves several steps and procedures. It is important to standardize the evaluation and reporting of usability procedures across studies to guide researchers, facilitate comparisons across studies, and promote high-quality usability studies. The first step to standardizing is to have an overview of how usability study procedures are reported across the literature. Objective This scoping review of reviews … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…There is a paucity of data on the sensitivity of usability testing methods [ 16 ], and optimal methods for specific eHealth solutions or cohorts have not been identified [ 11 ]. We therefore compared usability as reported by the quantitative and easy-to-use SUS with patient-rated confidence and investigator-rated independence in prespecified settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of data on the sensitivity of usability testing methods [ 16 ], and optimal methods for specific eHealth solutions or cohorts have not been identified [ 11 ]. We therefore compared usability as reported by the quantitative and easy-to-use SUS with patient-rated confidence and investigator-rated independence in prespecified settings.…”
Section: Discussionmentioning
confidence: 99%
“…In the broader context of chronic conditions, a recent systematic review concluded that the usability of wearable devices is poorly measured and reported [ 15 ]. Furthermore, there is no consensus regarding the methodology to assess usability in older adults, even though investigations about the sensitivity of different methods have been explicitly recommended [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the researcher conducting the usability evaluation received adequate training or is external to the team of researchers who developed the AAL solution is seldom reported by the studies included in this review. However, this information is of great relevance as both the inexperience of the researcher and a potential conflict of interest might impact the results of the usability evaluation [80]. Usability evaluation involves close interaction between the researcher and the participants, methods and procedures are complex and depend on this interaction and, therefore, require experience and knowledge to be assessed effectively as well as independence to minimize the potential for unwantedly influencing participants [80].…”
Section: Discussionmentioning
confidence: 99%
“…Among other requirements, there is a need to comply with established methodological guidelines, standardized study designs, and use of reporting checklists to ensure a detailed description of study methods and resulted data [83]. An example of guidelines that can be used to inform both study design and study reporting, in addition to the CAUSS which was used in the present study as a guide for methodological quality assessment, is suggested by our team in a previous publication [80]. This proposed a guide to consider when designing and reporting a user-centered usability evaluation study and includes aspects such as the characteristics of the person conducting the usability evaluation that should be reported, characteristics of the participants assessing the digital solution that should be reported, aspects of methods and techniques used and environment where the usability evaluation is taking place.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, 244 interface recommendations were identified, and they formed the basis for this study [ 32 ]. The identification of the 244 recommendations combined multiple sources: (1) our previous work [ 33 ], (2) a purposive search on Scopus database, and (3) inputs provided by experts in the field of interface design. The references identified through all 3 steps were extracted into an Excel (Microsoft) database with a total of 1210 recommendations.…”
Section: Introductionmentioning
confidence: 99%